Transcriptome-wide identification of altered RNA m6A profiles in cardiac tissue of rats with LPS-induced myocardial injury - Wang, Wei; Zhang, Tie-Ning; Yang, Ni; Wen, Ri; Wang, Yu-Jing; Zhang, Bing-Lun; Yang, Yu-Hang; Liu, Chun-Feng (Frontiers in Immunology, 2023)
Purpose Myocardial injury is a common complication in patients with endotoxaemia/sepsis, especially in children. Moreover, it develops through an unclear pathophysiological mechanism, and effective therapies are lacking. Recently, RNA modification, particularly N6-methyladenosine (m6A) modification, has been found to be involved in various physiological processes and to play important roles in many diseases. However, the role of m6A modification in endotoxaemia/sepsis-induced myocardial injury is still in its infancy. Therefore, we attempted to construct the m6A modification map of myocardial injury in a rat model treated by lipopolysaccharide (LPS) and explore the role of m6A modification in LPS-induced myocardial injury. Method Myocardial injury adolescent rat model was constructed by intraperitoneal injection of LPS. m6A RNA Methylation Quantification Kit was used to detect overall level of m6A modification in rat cardiac tissue. m6A-specific methylated RNA immunoprecipitation followed by high-throughput sequencing (MeRIP-seq) and RNA sequencing (RNA-seq) were conducted to identify the altered m6A-modified genes and differentially expressed genes in cardiac tissue of rats treated by LPS and control rats (6 versus. 6). Bioinformatics was used to analyze the functions of differentially m6A modified genes, differentially expressed genes, and genes with both differential m6A modification and differential expression. qPCR was used to detect expression of m6A modification related enzymes. Result We found that the overall level of m6A modification in cardiac tissue of the LPS group was up-regulated compared with that of the control group. MeRIP-seq and RNA-seq results showed that genes with differential m6A modification, genes with differential expression and genes with both differential m6A modification and differential expression were closely associated with inflammatory responses and apoptosis. In addition, we found that m6A-related enzymes (Mettl16, Rbm15, Fto, Ythdc2 and Hnrnpg) were differentially expressed in the LPS group versus. the control group. Conclusion m6A modification is involved in the pathogenesis process of LPS-induced myocardial injury, possibly through the regulation of inflammatory response and apoptosis-related pathways. These results provide valuable information regarding the potential pathogenic mechanisms underlying LPS-induced myocardial injury.